Filling the gap between the OR and virtual simulation: a European study on a basic neurosurgical procedure - Perin, Alessandro; Galbiati, Tommaso Francesco; Gambatesa, Enrico; Ayadi, Roberta; Orena, Eleonora Francesca; Cuomo, Valentina; Riker, Nicole Irene; Falsitta, Lydia Viviana; Schembari, Silvia; Rizzo, Stefano; Luciano, Cristian; Cappabianca, Paolo; et al. (Acta neurochirurgica, 2018)
Background Currently available simulators are supposed to allow young neurosurgeons to hone their technical skills in a safe environment, without causing any unnecessary harm to their patients caused by their inexperience. For this training method to be largely accepted in neurosurgery, it is necessary to prove simulation efficacy by means of large-scale clinical validation studies. Methods We correlated and analysed the performance at a simulator and the actual operative skills of different neurosurgeons (construct validity). We conducted a study involving 92 residents and attending neurosurgeons from different European Centres; each participant had to perform a virtual task, namely the placement of an external ventricular drain (EVD) at a neurosurgical simulator (ImmersiveTouch). The number of attempts needed to reach the ventricles and the accuracy in positioning the catheter were assessed. Results Data suggests a positive correlation between subjects who placed more EVDs in the previous year and those who get better scores at the simulator ( p = .008) (fewer attempts and better surgical accuracy). The number of attempts to reach the ventricle was also analysed; senior residents needed fewer attempts (mean = 2.26; SD = 1.11) than junior residents (mean = 3.12; SD = 1.05) ( p = .007) and staff neurosurgeons (mean = 2.89, SD = 1.23). Scoring results were compared by using the Fisher’s test, for the analysis of the variances, and the Student’s T test. Surprisingly, having a wider surgical experience overall does not correlate with the best performance at the simulator. Conclusion The performance of an EVD placement on a simulator correlates with the density of the neurosurgical experience for that specific task performed in the OR, suggesting that simulators are able to differentiate neurosurgeons according to their surgical ability. Namely this suggests that the simulation performance reflects the surgeons’ consistency in placing EVDs in the last year.